The investment opportunity set, director ownership, and corporate policies: evidence from an emerging market - Ho, Simon S.M; Lam, Kevin C.K; Sami, Heibatollah (Journal of Corporate Finance, 2004)
This paper provides evidence of the association between a firm's investment opportunity set (IOS), director ownership, and corporate policy choices. Using a sample of growth and non-growth firms in an emerging Asian market, we find that the IOS theory has significant explanatory power in the financing, dividend, executive compensation, and leasing aspects of corporate policies. Growth firms have lower debt-to-equity ratios and dividend yields, pay higher cash compensation and bonus amounts to their top executives, and finance a higher proportion of their asset acquisitions through operating leases. We also find that director ownership moderates and counteracts the association between IOS and corporate policies. Our results are consistent with contracting theory predictions that high director ownership mitigates the need for incentive or bonus compensation plans in growth firms.